The relationship between perceived discrimination, organisation-based self-esteem (OBSE) and job satisfaction among women at work. - Bhana, Sarika (My University, 2014)
The study aimed to test whether or not Organisational-based Self-Esteem (OBSE) mediated the relationship between perceived discrimination and job satisfaction. OBSE was expected to have an impact on Job Satisfaction, whilst Perceived Discrimination was argued to have an effect on OBSE. The study was conducted with a sample of 238 women as previous research indicates women are more likely to experience discrimination in the workplace. Contrary to expectations, the SEM revealed that perceived discrimination did not have a significant impact on job satisfaction. Also, the results obtained suggest that OBSE does not mediate the relationship as there was no significant relationship between perceived discrimination and OBSE. There was evidence that OBSE could be a moderator in the relationship instead. Furthermore, opposing the literature, the results supported the notion of global SE mediating the relationship between perceived discrimination and job satisfaction as it was the only significant path in the SEM. Overall, the study contributed to a body of literature and added value by suggesting that the role of perceived discrimination is underestimated as its impact extend outside of the workplace and may have deeper repercussions.
Keywords: Job satisfaction--South Africa.; Organizational behavior--South Africa.; Self-esteem--South Africa.; Women employees--South Africa.; Sex discrimination against women--South Africa.